Use of the Orac-Pyrogallol Red/Orac-Fluorescein Ratio to Assess the Quality of Antioxidants in Chilean Wines - Lissi-Gervaso, E (2011)
We have recently proposed that ORAC (Oxygen Radical Absorbance Capacity) methods employing fluorescein (ORAC-FL) and pyrogallol red (ORAC-PGR) as target molecules could be considered as complementary indexes. In particular, the ratio ORAC-PGR/ORAC-FL would reflect the average quality of the antioxidants present in a particular sample. In the present work, we evaluated the antioxidant capacity and the total phenol content of twelve Chilean wines (red, rose, and white) employing ORAC and Folin-Ciocalteau methods, respectively. Red wines showed higher Folin and ORAC values than rose and white wines. However, the ORAC-PGR/ORAC-FL ratio of all tested wines was close to 0.5. The results show that it is important to consider both, the phenol content of the sample (measured by ORAC-FL or Folin indexes) and their average reactivity (measured by the ORAC-PGR/ORAC-FL ratio). Both factors are considered relevant in the evaluation of the antioxidant capacity of wines.